Factors influencing inpatient duration among insanity acquittees in a Malaysian mental institution - Chan, Lai Fong; Phang, Cheng Kar; Loo, Tsui Huei; Ong, Lieh Yan; Mohd Daud, Tuti Iryani; Zakaria, Hazli; Singh, Suarn; Mohd Salleh, Rabaiah (ASEAN Federation for Psychiatry and Mental Health, 2010)
Objective: According to Malaysian law, defendants found not guilty by reason of insanity may be admitted to a psychiatric hospital and discharge is subject to the state ruler’s assent. The objective of this study is to examine the clinical, socio-demographic and forensic factors that influence inpatient duration of insanity acquittees in a Malaysian mental institution. Methods: This is a cross-sectional study of one hundred and twelve insanity acquittee inpatients in Hospital Bahagia Ulu Kinta from January 2007 to February 2007. Patients with a clinical diagnosis of schizophrenia, major depressive disorder and bipolar disorder were assessed using the Positive and Negative Syndrome Scale (PANSS), Hamilton Depression Rating Scale (HAMD) and Young Mania Rating Scale (YMRS) respectively. Other relevant socio- demographic, clinical and forensic factors were also assessed. Results: The inpatient duration varied widely from three months to forty-seven years with a median of seven years. Seventy five percent of patients were in remission. According to the multiple linear regression model, the strongest predictor of a longer duration of hospital stay for insanity acquittees was older age (p<0.001) followed by murder as the index offence (p=0.005). Good family support predicted a shorter inpatient duration. This model explains 56% of the variance in the inpatient duration. Conclusion: Social factors such as family support may be increasingly important in determining the discharge process of insanity acquittees besides clinical rehabilitation. Issues such as stigma of violent forensic patients and the role of community forensic rehabilitation services need to be further explored.